Complementary Therapy Interventions for Sleep Disturbances in Chronic Kidney Disease Patients on Hemodialysis: A Systematic Review - Tata Mahyuvi; Mardiyono, Mardiyono; Arief Candra Permana; Muhamad Ridlo; Agus Purnama (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Poor sleep quality is prevalent among chronic kidney disease (CKD) patients, particularly those undergoing hemodialysis, significantly impacting their quality of life, mental health, and mortality risk. Complementary therapies such as aromatherapy, guided imagery, music therapy, and progressive muscle relaxation have shown efficacy in reducing anxiety and improving sleep in chronic illness populations. This systematic review aimed to evaluate the effectiveness of various complementary therapies for managing sleep disturbances, anxiety, and quality of life in hemodialysis patients. Following PRISMA guidelines, we analyzed peer-reviewed English articles (2015–2025) sourced from Google Scholar, Scopus, Web of Science, and Crossref. Screening and data extraction were conducted by two independent reviewers to ensure rigor. The final synthesis of ten studies (six RCTs, two quasi-experimental, and two cross-sectional) indicates that non-pharmacological interventions, notably acupressure, offer a safe and holistic approach to enhancing sleep quality. These findings support Orem’s Self-Care Deficit Nursing Theory by emphasizing patient empowerment in symptom management.